Time living with food insecurity and socio-demographic factors: longitudinal analysis in a city in the semi-arid region of Northeast Brazil - Ana Beatriz Macêdo Venâncio dos Santos; Poliana de Araújo Palmeira; Angelo Giuseppe Roncalli da Costa Oliveira (Cambridge University Press, 2024)
Abstract Objective: Food insecurity (FI) is the lack of daily access for everyone to quality food in sufficient quantity. In many populations, it presents as a chronic and persistent condition. This study analysed the association between the length of time living with FI and socio-demographic conditions in households in a semi-arid municipality in the Brazilian Northeast between 2011 and 2019. Design: This is a population-based cohort study among families in the municipality in Northeast Brazil (2011, 2014 and 2019). FI was estimated through the Escala Brasileira de Insegurança Alimentar (EBIA, Brazilian Household Food Insecurity Measurement Scale), and the longitudinal category of time of living with FI was adopted to classify them according to the time they remained in FI during the cohort. The association with the socio-demographic profiles of the population was verified through multinomial logistic regression. Setting: Households in semi-arid, Northeast of Brazil. Participants: Household respondents interviewed in 2011, 2014 and 2019 (n 274). Results: Sixty-seven percentage (67 %) of families lived in FI in this period. Rural residence, low monthly per capita income and low schooling of the household reference person increased the chances of these families living longer in FI. These overlapping conditions increased the odds of FI in the household. Conclusions: Coping with FI requires intersectoral intervention that improves the socio-demographic conditions of the population.